Caracterização de bioconjugados de pontos quânticos de ZnCdTe com a lectina de Canavalia brasiliensis - Santiago, Mayara Queiroz de (2016)
In recent years, researchers have focused their effort to the development of techniques with an interest in diagnostic strategies. To understand the onset and progression of various diseases before the action of any drug is necessary to evaluate the interactions of biological molecules in various cellular processes, this can be done by the use of biomarking strategies. Quantum dots (QDs) are fluorescent inorganic semiconductor compounds, which exhibit quantum confinement in three dimensions and unique optical properties and may be used in the imaging and detection of diagnostic signals. Lectins, proteins/glycoproteins that interact reversibly to specific carbohydrates, are already applied in several studies of biological activities due to its recognition properties. In view of this, the objective of this work was the bioconjugation of quantum dots ZnCdTe with the lectin of Canavalia brasiliensis (ConBr), the physicochemical characterization, evaluation of fluorescence properties and hemagglutination the formed system. The ZnCdTe synthesized nanoparticles were functionalized with a glutaraldehyde linker and then, submitted to bioconjugation reaction with the lectin. The obtained system ZnCdTe-ConBr was subjected to various analyzes such as particle size by Dynamic Light Scattering (DLS); evaluation of optical properties by UV/Visible Spectroscopy Absorption (UV/Vis) and photoluminescence spectroscopy; chemical evaluation of bioconjugation by Infrared Spectroscopy (FT-IR); assessment of morphology and microcomposition by Scanning Electron Microscopy (SEM); topographical evaluation, mechanical and physicochemical properties by Atomic Force Microscopy (AFM); and evaluation of lectin carbohydrate binding site integrity for haemagglutinating activity (H.A.). The results suggest that ZnCdTe-ConBr system was covalently conjugated after the reaction. It was also observed an increase in particle size and a greater homogeneity compared to non-conjugated quantum dots. The optical and functional properties of ZnCdTe-ConBr system was kept displaying a degree of high colloidal stability and functional over a period of 60 days. It was concluded that the system obtained here can be used as a biotechnological tool for use in diagnostic imaging technique.